2008
DOI: 10.1007/s10681-008-9732-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in yield, fiber quality, and photosynthesis of okra leaf oriented hybrid cotton (Gossypium hirsutum L.)

Abstract: Leaf shape is an important factor affecting canopy structure, photosynthetic characteristics, and yield. Introducing okra leaf shape is considered an important strategy in cotton heterosis breeding. The objective of the study was to evaluate the heterosis in okra leaf cotton hybrid F 1 s, which were developed by crossing two sterile near isolines and three restorer near isolines. A normal leaf check hybrid F 1 , Zhongza 29, and four newly developed okra leaf oriented hybrid F 1 s, including the superokra (seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Heterosis breeding is an effective tool to enhance the yield and enrich quality parameters (Srivastava 2000;Dutt et al 2004;Li 2005) and availability of CMS and restorer factors facilitated the production of cotton hybrids at commercial scale (Wang et al 2004;Zhang et al 2007). Useful heterosis has more practical implications as it conveys a more straightforward message to plant breeders and farmers, compared to mid-parent and best parent heterosis (Hua et al 1963;Dong et al 2007;Zhu et al 2008;Geddam et al 2011). In the present study, the performance of interspecific coloured cotton hybrids regarding yield was significantly higher than intraspecific hybrids, thus demonstrating the commercial potential of interspecific hybrids (Dutt et al 2004;Zhao & Wang 2005; Kantartzi & Roupakias 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterosis breeding is an effective tool to enhance the yield and enrich quality parameters (Srivastava 2000;Dutt et al 2004;Li 2005) and availability of CMS and restorer factors facilitated the production of cotton hybrids at commercial scale (Wang et al 2004;Zhang et al 2007). Useful heterosis has more practical implications as it conveys a more straightforward message to plant breeders and farmers, compared to mid-parent and best parent heterosis (Hua et al 1963;Dong et al 2007;Zhu et al 2008;Geddam et al 2011). In the present study, the performance of interspecific coloured cotton hybrids regarding yield was significantly higher than intraspecific hybrids, thus demonstrating the commercial potential of interspecific hybrids (Dutt et al 2004;Zhao & Wang 2005; Kantartzi & Roupakias 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The modern concept of heterosis (hybrid vigour) in crops was defined by Shull in 1908 (Randhawa & Singh 1994). Since then, many plant breeders have documented intraspecific and interspecific heterosis in cotton (Wang et al 2004;Wu et al 2004;Dong et al 2006Dong et al , 2007Zhu et al 2008; Kantartzi & Roupakias 2010;Geddam et al 2011) and found that interspecific crosses displayed more heterosis than intraspecific heterosis, thus having more commercial potential (Baloch et al 1993;Zhang et al 2007). The availability of cytoplasmic male sterility (CMS) and fertility restorer parents has facilitated highyield hybrid seed production throughout the world (Wang et al 2004;Zhang et al 2007;Zhu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The F 1 progeny of cotton performs strong heterosis in boll number, boll weight, and seed cotton yield. The hybrid seeds are widely produced in India and China [1]. However, the current cotton hybrid seeds are mainly produced through hand emasculation and pollination, which requires a large labor force and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Upland cotton ( Gossypium hirsutum L.) is one of the world's most important economic crops, producing mostly textile fiber and the second‐most valuable oil (Yin et al ). It has strong heterosis in boll number, boll weight, and seed cotton yield (Zhu et al ). The hybrid seeds are widely planted and propagated in India and China (Yin et al ).…”
Section: Introductionmentioning
confidence: 99%